THE FROBENIUS PROBLEM FOR MERSENNE NUMERICAL SEMIGROUPS - Rosales, J. C. (2020)
In this paper, we give formulas for the embedding dimension, the Frobenius number, the type and the genus for a numerical semigroups generated by the Mersenne numbers greater than or equal to a given Mersenne number.